Implementation Of Update Voter Data On Election Of Governor And Vice Governor Of Riau In Bengkalis Regency - Zainal Zainal; Rahmad Nuryadi Putra (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2022)
The direct election system will provide opportunities for citizens to actualize their political rights as candidates or candidates as well as voters who come from their status as citizens. So that there is interaction between fellow citizens in an effort to participate in both the General Election and Regional Head Elections. The implementation of the Regional Head Election is the main task of the General Election Commission, which authority is then delegated to the Regional General Election Commission. In order to ensure that the Regional Head Election is carried out democratically as mandated in Article 18 paragraph (4) of the 1945 Constitution, the sovereignty of the people must be respected as the main condition for the implementation of elections at the local level. However, not a few dynamics have occurred since the Presidential and Vice-Presidential Elections were held in 2004 and the Regional Head Elections in 2005. This is an early reflection of the Indonesian nation implementing direct elections as a form of citizen involvement in determining their fate at the national and regional levels. This study uses a descriptive research method with a qualitative approach. Qualitative descriptive research is a type of research with the process of obtaining data as it is. This study emphasizes the meaning of the results while the deductive approach is reasoning that starts from certain facts to general conclusions. The implementation of updating voter data in the Election of Governor and Deputy Governor of Riau in Bengkalis Regency in 2018 was carried out according to the stages starting from the preparation of updating data, matching and research, the Temporary Voter List and the Permanent Voter List. The results showed that all stages of updating voter data went smoothly so that the Bengkalis Regency KPU could establish a Permanent Voter List. However, behind the smooth stages of updating, there are still people who have the right to vote that are not registered in the DPT.